FINANCIAL STATEMENTS AUDITORS WORK EXPERIENCE DURING COVID-19 PANDEMIC: EVIDENCE FROM SERBIA - Kljajić, Maja; Perić, Miroslav (The European Journal of Applied Economics, 2023)
During the global pandemic auditors have not be able to perform full audit procedures due to social distancing measures. Therefore, mandatory audits were completed by accepting higher audit risk, with possibility of material misstatements being present within statements to some extent. Uncertainty and risk arising from the current environment have resulted in changes in reporting and audit procedures, although these areas are strictly governed by the legal and regulatory framework. This paper will analyse the existing guidelines on COVID-19 considerations related to financial statements audit, issued by global and national regulators and professional organisations. Namely, all ISA remain in effect and additionally COVID-19 related guidelines should be used as a supplementary material. Furthermore, the paper will present the results of the conducted survey. Mostly external auditors were participants in the survey, with the aim to assess impacts of the pandemic. Results show that most respondents claim that pandemic had an effect on the way audit process is being performed. However, only 7% of them believe that audit quality level is now higher. They named following audit areas as the ones being affected the most: going-concern principle assessment, audit risk assessment, audit evidence acquisition, and audit documentation and client file preparation.